Nivel de conocimiento de las gestantes en la prueba de tamizaje metabólico neonatal en la cooperativa las vegas del cantón Buena Fe. Primer semestre 2018 - Dominguez Zambrano, Ariel Steven (2018)
The knowledge of screening as such a set of information and knowledge acquired with the experience and education in the development of each person. The neonatal metabolic screening known in itself as a preventive health program since it helps to detect in a timely manner serious and irreversible diseases that can not be detected at birth. Objective: The research carried out identified the need to carry out the research with the objective of determining the level of knowledge about Neonatal Metabolic Screening in the pregnant women of Las Vegas Cooperative, Canton Buena Fe. Methodology. The investigation was descriptive - transversal, with a sample of 23 pregnant women. Results 87% of pregnant women are unaware of the diseases that are detected by the heel test. Conclusions. The surveyed pregnant women do not have enough knowledge about the Neonatal Metabolic Screening, so it is important to promote the screening in order that the institutions that give information use the means of communication to reach each place; thus helping the best quality of the children.